2010
DOI: 10.1002/ar.21054
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Quantitative Assessment of Long Bone Vascularization in the Adult Rat Using Microcomputed Tomography

Abstract: The objective of this study was to develop and validate a technique for both 3D imaging and quantification of the vascular network of bone tissue in the rat. Five month-old male Wistar rats were divided into tailsuspension (21 days) and control groups. Sixty percent barium sulfate solution was infused into the vena cava. The tibiae were evaluated in 2D and 3D before and after decalcification, using conventional microcomputerized tomography (lCT) at 10 and 5 lm resolution and synchrotron radiation (SR) lCT. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Micro-CT also provides three-dimensional (3D) images of bone architecture and various parameters that influence the strength of trabecular bone (e.g., trabecular bone volume, trabecular number, trabecular separation, trabecular thickness, and structure model index). However, because of the limited scan range, micro-CT is mostly used for the bones of small animals (rats or mice) or extracted human bones [12], [14], [15], and is applied more in laboratory-based research than in the clinical field of orthopedics. In clinical orthopedic practice, quantitative computed tomography (QCT) [5], [16], [17] or peripheral quantitative computed tomography (pQCT) [6], [9], [10], [18][20] are commonly used to assist in determining the bone BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-CT also provides three-dimensional (3D) images of bone architecture and various parameters that influence the strength of trabecular bone (e.g., trabecular bone volume, trabecular number, trabecular separation, trabecular thickness, and structure model index). However, because of the limited scan range, micro-CT is mostly used for the bones of small animals (rats or mice) or extracted human bones [12], [14], [15], and is applied more in laboratory-based research than in the clinical field of orthopedics. In clinical orthopedic practice, quantitative computed tomography (QCT) [5], [16], [17] or peripheral quantitative computed tomography (pQCT) [6], [9], [10], [18][20] are commonly used to assist in determining the bone BMD.…”
Section: Introductionmentioning
confidence: 99%
“…This is a disadvantage when studying bone and requires bone decalcification when using this contrast agent (Bentley et al ., ; Duvall et al ., ; Marxen et al ., ; Bolland et al ., ; Young et al ., ; Mondy et al ., , ; Nyangoga et al ., ; Roche et al ., ). We therefore chose barium sulphate for this study as recommended by a number of authors (Moore et al ., ; Duvall et al ., ; Marxen et al ., ; Oses et al ., ; Schneider et al ., ; Jia et al ., ; Roche et al ., ). We tested many mixtures, with different gelatin or barium sulphate percentages; the results were irrelevant or could not be reproduced.…”
Section: Discussionmentioning
confidence: 99%
“…We have made a lot of tests using these two contrast agents. Barium sulphate has been demonstrated to give better results as in the literature (Jia et al ., ; Prisby et al ., ; Roche et al ., , ) and was used in this study. Indeed, Microfil showed rounded artefacts, seems to change vascular anatomy and using it also need to decalcify the samples for study them by micro‐CT.…”
Section: Introductionmentioning
confidence: 98%
“…For example, recent work has shown that prolonged skeletal disuse in hindlimb unloaded rats induces a narrowing of the maximal diameter of the femur PNA (39) and rarefaction of the microvascular network (14), both of which result in a lower femoral bone and marrow perfusion and vascular conductance with reloading (39). In contrast, 10–12 wks of treadmill exercise training increases the maximal diameter of the femur PNA and enhances the PNA endothelium-dependent vasodilation (12).…”
Section: Discussionmentioning
confidence: 99%